The Role of Museums in Preserving Indigenous Art: A Comparative Study between India and Australia (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2022)
This research delves into the pivotal role that museums play in preserving and promoting indigenous art, with a comparative analysis between India and Australia. Indigenous art holds profound cultural significance, serving as a visual language that reflects the rich heritage and traditions of diverse communities. The study aims to explore the methods employed by museums in these two countries to safeguard and showcase indigenous art, considering the unique socio-cultural contexts that shape these efforts. The research methodology involves a comprehensive literature review, interviews with museum curators, and an analysis of exhibition spaces and curation practices in select museums in both nations. By employing a comparative approach, the study seeks to identify similarities and differences in the preservation strategies adopted by museums in India and Australia, shedding light on the effectiveness of these approaches in maintaining the integrity of indigenous art. The findings of this research contribute to a deeper understanding of the challenges and successes faced by museums in preserving indigenous art. Key areas of investigation include the incorporation of indigenous perspectives in exhibition curation, community engagement initiatives, the integration of new technologies, and the impact of governmental policies on museum practices.